A Critical Analysis of the Biodiesel Program in Brazil - Sergio N. Monteiro; Luciano B. Oliveira; Luis Guilherme C. Marques; Angela O. Costa (The Minerals, Metals and Materials Society, 2008)
"Biofuels are gaining a relevant role in today’s world not only as a solution for the decreasing petroleum reserves but mainly as a positive contribution to the efforts in global warming mitigation. In Brazil, since 1975, the replacement of gasoline by ethanol started a so-called PROALCHOOOL program, which is now being complemented with the replacement of petroleum diesel by biodiesel. This biodiesel program was officially created in 2005 with mandatory goals, supported by legislation, of 2% addition in 2008 and 5% addition in 2013 into all commercialized regular diesel. In this work, a critical analysis of the Brazilian biodiesel program is presented. The technical aspects related to the different raw materials, including wastes, available for biodiesel conversion as well as the economical conditions associated with production costs and market logistic are discussed. The environmental benefits associated with the retention of greenhouse gases are also discussed.IntroductionToday the commonly accepted fact that the petroleum world reserves are probably passing through a maximum and start declining in terms of the total amount that can be extracted by existing technologies is motivating significant changes in our society. The continuous increase in the price of gasoline and other liquid fuels is an immediate worrisome and visible consequence. However, more than an economical problem, our civilization is already facing the effects of global warming, due to CO2 emission from burning fossil fuels, mainly from coal and petroleum. It is now realized that a large scale solution for these problems demands the prompt substitution of non-renewable fossil fuels by others that, in addition of being renewable, have a relatively lower contribution to the greenhouse gases."